Further Studies on Homo- and Copolymerization of Styrene Through Cpticl3-Mao Initiator System - Rabagliati-Canessa, F; Zapata-Ramirez, P; Canales-Arévalo, D (Sociedad Chilena de Quimica, 2013)
The copolymerization of styrene with cyclohexene, 1-methyl-1-cyclohexene and with norbornene at various styrene/comonomer molar ratio, using cyclopenta-dienyltitanium trichloride and methylaluminoxane, CpTiCl3-MAO, initiating system has been tested. Only the couple styrene-norbornene produce real styrene-norbornene copolymers, while comonomers cylohexene and 1-methyl-1-cyclohexene only yielded syndiotactic polystyrene, s-PS. The present paper also report results of exploratory experiments on the synthesis through in-situ polymerization of nanocomposites based on styrene/para-methylstyrene copolymer, S/p-MeS, including SiO2 nanoparticles where nanocomposites with modified SiO2 nanoparticles, showed a better dispersion of nanoparticles in the copolymer matrix.